2012
DOI: 10.1016/j.ejop.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A genomic survey shows that the haloarchaeal type tyrosyl tRNA synthetase is not a synapomorphy of opisthokonts

Abstract: The haloarchaeal-type tyrosyl tRNA synthetase (tyrRS) have previously been proposed to be a molecular synapomorphy of the opisthokonts. To re-evaluate this we have performed a taxon-wide genomic survey of tyrRS in eukaryotes and prokaryotes. Our phylogenetic trees group eukaryotes with archaea, with all opisthokonts sharing the haloarchaeal-type tyrRS. However, this type of tyrRS is not exclusive to opisthokonts, since it also encoded by two amoebozoans. Whether this is a consequence of lateral gene transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The monophyletic grouping of Opisthokonta is well supported by both molecular trees (Baldauf et al 2000; Lang et al 2002; Medina et al 2003; Ruiz-Trillo et al 2004; Ruiz-Trillo et al 2008; Steenkamp and Baldauf 2004; Steenkamp et al 2006; Torruella et al 2012) and molecular synapomorphies, such as a 12 amino acid insertion in the elongation 1 alpha (EF1-alpha) gene (Baldauf and Palmer 1993; Steenkamp and Baldauf 2004) and a haloarchaeal-type tyrosyl tRNA synthetase (Huang et al 2005, but see Shadwick and Ruiz-Trillo 2012). These molecular analyses also tend to divide the opisthokonts into two clades: the Holozoa (Lang et al 2002), which includes the Metazoa and their unicellular relatives, and the Holomycota (Liu et al 2009, also named Nucletmycea (Brown et al 2009), which contains the fungi, nucleariids, and F. alba .…”
Section: Introductionmentioning
confidence: 97%
“…The monophyletic grouping of Opisthokonta is well supported by both molecular trees (Baldauf et al 2000; Lang et al 2002; Medina et al 2003; Ruiz-Trillo et al 2004; Ruiz-Trillo et al 2008; Steenkamp and Baldauf 2004; Steenkamp et al 2006; Torruella et al 2012) and molecular synapomorphies, such as a 12 amino acid insertion in the elongation 1 alpha (EF1-alpha) gene (Baldauf and Palmer 1993; Steenkamp and Baldauf 2004) and a haloarchaeal-type tyrosyl tRNA synthetase (Huang et al 2005, but see Shadwick and Ruiz-Trillo 2012). These molecular analyses also tend to divide the opisthokonts into two clades: the Holozoa (Lang et al 2002), which includes the Metazoa and their unicellular relatives, and the Holomycota (Liu et al 2009, also named Nucletmycea (Brown et al 2009), which contains the fungi, nucleariids, and F. alba .…”
Section: Introductionmentioning
confidence: 97%
“…We do not aim to infer a eukaryotic tree of life from the myosin genomic content ( Richards and Cavalier-Smith 2005 ; Odronitz and Kollmar 2007 ). Convergence ( Zmasek and Godzik 2012 ) (discussed later), gene fission ( Leonard and Richards 2012 ), duplication, gene loss ( Zmasek and Godzik 2011 ), and horizontal gene transfer (HGT) ( Andersson et al 2003 ; Andersson 2005 ; Marcet-Houben and Gabaldón 2010 ; Richards et al 2011 ) are important phenomena in eukaryotes and, therefore, molecular markers such as the distribution pattern of gene orthologs need to be tested using gene phylogeny and updated as new genome sequences are released ( Dutilh et al 2007 ; House 2009 ; Shadwick and Ruiz-Trillo 2012 ). We based our myosin classification exclusively on phylogenetic affinity, which allowed us to identify: gene and domain loss, paralog groups, and convergent evolution of gene domain architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Inferring the transfer of single genes among divergent lineages of eukaryotes based on the topology of single gene trees is challenging given that we would be asking approximately 200-300 amino acids to estimate events as old as approximately 1.8 billion years (an estimate of the timing of eukaryotic origins [38,39]). In addition, errors in phylogenetic reconstruction such as long branch attraction and incomplete taxon sampling can mislead interpretations of lateral events based on tree topologies [22,40,41]. Perhaps most importantly for the analyses presented here, the prevalence of gene loss over evolutionary time [42] confounds interpretation of lateral events as genes present in bacteria plus only a few non-sister eukaryotic lineages may have been lost in other eukaryotic lineages.…”
Section: Inferences About Lateral and Endosymbiotic Gene Transfermentioning
confidence: 97%
“…The impact of taxon sampling on inferences about ancient LGT can be seen in the changing narrative about a single gene transfer of a tyrosyl-tRNA synthetase gene, which was originally argued to be a synapomorphy for Opisthokonta based on available data [61]. Reanalysis with data from additional microbial eukaryotes revealed that this gene was also present in Amoebozoa [40]. In our expanded taxon sampling, we find this gene in multiple lineages in Amoebozoa plus the parasite Blastocystis homoni (Sr_st), the orphan lineage Palpitomonas bilix (EE_is_Pbil) and two Rhizarian species (Sr_rh; electronic supplementary material, figure S1).…”
Section: Numerous Caveats Must Be Considered When Interpreting Pattermentioning
confidence: 99%